The combination of nutraceutical and simvastatin enhances the effect of simvastatin alone in normalising lipid profile without side effects in patients with ischemic heart disease. (June 2016) - Campolongo, Giuseppe; Riccioni, Costanza Valentina; Raparelli, Valeria; Spoletini, Ilaria; Marazzi, Giuseppe; Vitale, Cristiana; Volterrani, Maurizio
Abstract: Background: hyperlipidemia is one of the most important cardiovascular risk factors. Statins at high doses are commonly prescribed to lower LDL-cholesterol, but are often poorly tolerated. In particular, muscle pain and increase of creatine phosphokinase are frequent side effects. The purpose of this study was to assess whether the addition of a nutraceutical to simvastatin may result in the achievement of the therapeutic target (LDL-cholesterol less than 70 mg/dL) without side effects in patients with ischemic heart disease. Methods: Sixty-four patients with ischemic heart disease treated with simvastatin 20 mg who had not achieved the therapeutic target were enrolled. Patients were randomised 1:1. Patients of group A (n = 32) were given simvastatin 40 mg per day and patients of group B (n = 32) were given simvastatin 20 mg plus 2 tablets of a nutraceutical composed of bergamot, phytosterols, artichoke, vitamin C. Results: After 3 months, patients in both groups showed a significant reduction from baseline in total cholesterol, LDL-c and tryglicerides. However, in group A, 4 patients reported myalgia (9, 7%) with an increase in creatine phosphokinase; whereas no adverse events occurred in group B. Conclusions: The association of a nutraceutical and simvastatin 20 mg may be a valid therapeutic option for the treatment of hyperlipidemia in patients with ischemic heart disease intolerant to statin at high doses, in the absence of side effects. Further studies are needed to clarify the mechanisms of action of nutraceuticals.